Interpersonal relations during birth: perceptions of adolescentes - Heitor Silva Biondi; Nalú Pereira da Costa kerber; Diogo Henrique Tavares; Eliana Cardia de Pinho; Bruna Goulart Gonçalves; Letícia Amico Marques (Universidade Federal de Santa Maria, 2019)
Objective: To know the perception of the adolescents about the interpersonal relations established with the professionals of an Obstetric Center. Method: Descriptive exploratory qualitative study. Sixty-two teenagers who had a child in a University Hospital in southern Brazil were interviewed. Data were analyzed through Content Analysis, and one sought to visualize the different professional roles described by Peplau. Results: The interpersonal relationship established with interaction based on respect, cordiality, patience, solicitude, constant presence, willingness to respond to questions, and actions to convey tranquility and calm are satisfactory aspects. However, detachment, disinformation, disrespect and hostility also emerged. The emergence of negative elements seems to be linked to the personal postures of professionals. Final Considerations: Interpersonal relationships are not understood as a fundamental part of childbirth care, and are no longer fully explored as part of the care, remaining in the background and compartmentalizing childbirth care.